The Study of Dried Ginger and Linggan Wuwei Jiangxin Decoction Treatment of Cold Asthma Rats Using GC–MS Based Metabolomics - Ran, Shan; Sun, Fangfang; Song, Yan; Wang, Xiaoli; Hong, Yan; Han, Yanquan (Frontiers in Pharmacology, 2019)
Dried ginger is monarch drug in Linggan Wuwei Jiangxin decoction prescription,which both treat cold asthma in clinic.The study was to investigate and compare the effects of dried ginger and Linggan Wuwei Jiangxin decoction against cold asthma rats at metabolomics level using GC-MS.OVA and ice water induced cold asthma was developed in SD rats.The effects of dried ginger and Linggan Wuwei Jiangxin decoction were evaluated by general morphological observation,hematoxylin eosin staining, inflammatory cell count and Ig-E,IL-4,IFN-γ and visceral index. The metabolomics based on GC-MS with multivariate statistical analysis was performed. Biomarker identification, pathways analysis,correlation relationship between identified biomarker and efficacy indexes were carried out successively.The results show that dried ginger and Linggan Wuwei Jiangxin decoction have obvious effects on cold asthma rats.37 metabolites (15 in serum and 22 in urine) possibly contributing to the progress of cold asthma were identified. These metabolites mainly involve carbohydrate,fatty acids and their products,organic acid and others.Seven pathways were involved by MetaboAnalyst 4.0 metabolic pathway analysis.After intervention by dried ginger and Linggan Wuwei Jiangxin decoction,the majority of altered metabolites and metabolic pathway were effectively reversed, and Linggan Wuwei Jiangxin decoction regulated more metabolite of carbohydrate and fatty acid which contribute to energy metabolism and oxidative stress in cold asthma than these of dried ginger.It was concluded that dried ginger and Linggan WuWei Jiangxin decoctionboth produced the beneficial effects on cold asthma; Linggan Wuwei Jiangxin decoction has more powerful effects than dried ginger on cold asthma.The study explored the effect of dried ginger and Linggan Wuwei Jiangxin decoction on cold and asthma from the metabolomics level.In addition,it provides a reference for the research on the compatibility of Chinese Medicine.